Determination of Efficacy of Smizyme TS G5 2,500 Phytase in Nursery Pigs - M. R. Wensley; J. C Woodworth; J. M. DeRouchey; S. S. Dritz; M. D. Tokach; R. D. Goodband; J. Faser (Kansas Agricultural Experiment Station Research Reports, 2019)
A total of 320 nursery pigs (DNA; 241 × 600; initially 22.9 lb BW) were used in a 21-d growth trial to determine the available P (aP) release curve for Smizyme TS G5 2,500 (Origination, Inc., Saint Paul, MN). Pigs were weaned at approximately 21 d of age, randomly allotted to pens based on initial body weight (BW), and fed common starter diets. On d 21 post-weaning, considered d 0 of the study, pens were blocked by BW and randomly allotted to 1 of 8 dietary treatments with 5 pigs per pen and 8 pens per treatment. Eight 1-ton batches of basal diet were manufactured and subsequently divided to be the major portion of experimental diets. Dietary treatments were formulated to include increasing aP derived from either an inorganic P source (0.12%, 0.18%, or 0.24% from monocalcium P) or increasing phytase (150, 250, 500, 750, or 1,000 FTU/kg). Diets were corn-soybean meal-based and contained 1.24% standardized ileal digestible (SID) lysine with other amino acids set to meet or exceed NRC requirement estimates. Prior to beginning the 21-d study, all pigs were fed the negative control diet containing 0.12% aP for a 3-d period (d 18 to 21 post-weaning). Diets containing phytase were submitted for complete phytase analysis (Eurofins Scientific Inc., Des Moines, IA) using the AOAC official method 2000.12 and analyzed concentrations were 190, 310, 500, 790, or 850 FTU/kg. On d 21 of the experiment, the pig closest to the mean BW in each pen was euthanized and the right and left fibula were collected to determine bone ash. One fibula from each animal was processed with defatting, and the other fibula was processed without defatting. Overall (d 0 to 21), pigs fed increasing aP from inorganic P or phytase had improved (linear,P<0.01) average daily gain (ADG), feed efficiency (F/G), and final BW. Additionally, pigs fed increasing aP from phytase had increased (linear,P<0.01) average daily feed intake (ADFI). For the defatted bones, pigs fed increasing aP from inorganic P had increased (linear,P<0.01) bone ash weights, resulting in increased (quadratic,P<0.01) percentage bone ash, while those fed increasing levels of phytase had increased (linear,P<0.01) bone ash weights and percentage bone ash. Similarly, using the non-defatted analytical method, pigs fed increasing aP from either inorganic P or phytase had increased (linear,P<0.01) bone ash weights and percentage bone ash. The aP release increased (linear,P<0.01) for all criteria up to the highest phytase dose when using ADG, F/G, or bone ash weight as the indicator of release, in contrast to using percentage bone ash of defatted bones which increased in a quadratic fashion (P<0.05). In conclusion, the magnitude of aP release at different FTU inclusion rates depends on the response criteria, but Smizyme TS G5 2,500 appears to have a similar aP release to other commercially available phytase sources.
Keywords: nursery pig; bone ash; phosphorus; phytase